Makna Tanah Leluhur Bagi Naomi Berdasarkan Teks Rut 1:1-22 - Nelci Nafalia Ndolu; Marsi Bombongan Rantesalu (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2019)
The Meaning of Ancestral Land For Naomi Based on Ruth 1: 1-22. The story of Naomi in Ruth 1: 1-22 is closely related to her ancestral land in Bethlehem-Judah. In Ruth 1: 1-3, Naomi is told to make a choice to leave her ancestral land. But Ruth 1: 6 explains that Naomi finally chose to return to her ancestral lands in Bethlehem-Judah after experiencing various suffering and tragedies in the land of Moab. Naomi's choice implied Naomi's perception of the economic, cultural, political and religious meaning of her ancestral land. Based on Ruth 1: 6-19-22, Naomi continues to acknowledge her ancestral land as the "mother" who gave birth to her, always faithfully welcomes her return, treats all the pain of her life; and even guarantee the prosperity of his life, the place that guarantees the rights of life and the social as a widow, and a safe place to worship faithfully to Allah the giver and the owner of his ancestral land. Makna Tanah Leluhur Bagi Naomi Berdasarkan Rut 1:1-22. Kisah Naomi dalam Rut 1:1-22 berkaitan erat dengan tanah leluhurnya di Betlehem-Yehuda. Dalam Rut 1:1-3, Naomi dikisahkan membuat pilihan untuk meninggalkan tanah leluhurnya. Namun Rut 1:6 menjelaskan bahwa Naomi akhirnya memilih untuk kembali ke tanah leluhurnya di Betlehem-Yehuda setelah mengalami berbagai penderitan dan tragedi di Moab tanah rantau. Pilihan Naomi tersebut tersirat persepsi Naomi tentang makna ekonomis, budaya, politis dan religious dari tanah leluhurnya. Berdasarkan Rut 1:6-19-22, Naomi tetap mengakui tanah leluhur nya sebaga “ibu” yang telah melahirkannya, selalu setia menyambut kepulangannya, mengobati semua kepedihan hidupnya; dan bahkan menjamin kesejahtraan hidupnya, tempat paling menjamin hak-hak hidup dan sosial sebagai seorang janda, dan tempat yang aman untuk beribadah dengan setia kepada Allah sang pemberi dan pemilik tanah leluhurnya.